Is a bad mentor better than no mentor?. (16th September 2020) - Jung, Jiwon; Bozeman, Barry
Mentoring is generally touted as beneficial, yet not all mentoring is good, and the literature gives scant attention to the effects of quality of mentoring on career outcomes. Our study aims to close the gap by providing a comparison among three groups - employees with a good mentor, a bad mentor, and no mentor at all. The study finds that for more than 3, 000 respondents, those with a mentor, even a bad one, enjoy the benefits of mentorship. However, the idea that having a bad mentor is better than no mentorship is only partly correct - it is contingent on just how bad and bad in what ways. The quality of the mentoring experience influences job satisfaction more while a mere presence of a mentor is important for the salary of the protégés. Furthermore, mentored public sector workers, unlike workers in the private and non-profit sectors, have a lower salary and job satisfaction compared to those who have no mentor. We provide suggestions about what may account for this unexpected and curious finding.